Effect of gamma irradiation on X‐ray absorption and photoelectron spectroscopy of Nd‐doped phosphate glass. (12th October 2016) - Rai, V. N.; Rajput, Parasmani; Jha, S. N.; Bhattacharyya, D.; Raja Shekhar, B. N.; Deshpande, U. P.; Shripathi, T.
Abstract : Gamma irradiation was found to change the elemental concentration of the atoms in Nd‐doped phosphate glass The intensity of the white line in the XANES spectrum correlated with the ratio O/Nd in the glass matrix. The ratio of non‐bridging oxygen to total oxygen in the glass after gamma radiation correlated with the concentration of defects in the glass samples. Glasses having a higher concentration of oxygen were found to be soft to gamma irradiation. Abstract : X‐ray absorption near‐edge structure (XANES) and X‐ray photoelectron spectroscopy (XPS) of Nd‐doped phosphate glasses have been studied before and after gamma irradiation. The intensity and the location of the white line peak of the L 3 ‐edge XANES of Nd are found to be dependent on the ratio O/Nd in the glass matrix. Gamma irradiation changes the elemental concentration of atoms in the glass matrix, which affects the peak intensity of the white line due to changes in the covalence of the chemical bonds with Nd atoms in the glass (structural changes). Sharpening of the Nd 3 d 5/2 peak profile in XPS spectra indicates a deficiency of oxygen in the glasses after gamma irradiation, which is supported by energy‐dispersive X‐ray spectroscopy measurements. The ratio of non‐bridging oxygen to total oxygen in the glass after gamma radiation has been found to be correlated to the concentration of defects in the glass samples, which are responsible for its radiation resistance as well as for its coloration.